DESIGN OF INDUSTRIAL HALLS WITH A STEEL STRUCTURE DUE TO AN ACCIDENTIAL DESIGN SITUATION - THE IMPACT OF A VEHICLE ON A FRAME COLUMN (Collection of scientific works «Modern structures of metal and wood», 2024)
The article presents the effect of vehicle impact on the behaviour of the steel structure of an industrial hall. A portal industrial hall with a span of 18.0 m, a length of 42.0 m and a column height  of  7.0  m  was  considered.  The  spacing  of  the  frames  -  the  main  transverse  systems  -  was assumed equal to 6.0 m. The case in which a truck hits a frame column was considered. A scenario was assumed in which the impact occurs when the vehicle leaves the manoeuvring area located at the industrial hall. Therefore, according to EN 1991-1-7, the speed of the vehicle is 10 km/h. The weight of the vehicle was assumed to be 20000 kg. The direction of impact was assumed perpendicular to the side wall of the hall. The calculations were carried out in two stages. The first - optimization of cross sections of beams and columns in a permanent design situation. Static analysis was used. The second - determination of internal forces from impact in an accidental design situation. Dynamic analysis was used. Hall structural systems made of HEA, HEB and IPE sections were considered. The pinned and rigid connection of the column to the foundation was considered. The calculations were performed using Autodesk's Robot Structural Analysis 2024 computer software.